2019
DOI: 10.1021/acsmedchemlett.8b00624
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anthraquinone Compounds Induce Cancer Cell Death through Paraptosis

Abstract: Novel anthraquinone compounds that induce ER stress and paraptosis-like cell death were designed and synthesized. Compound 4a is the first organic micromolecule to kill tumor cells by only paraptosis, and its mechanism of action has been further explored. Paraptosis does not appear to involve either phosphatidylserine translocation associated with apoptosis or cell cycle arrest. The bisbenzyloxy and N-(2hydroxyethyl)formamide structures may be two critical pharmacophores for paraptosis. Bisbenzyloxy can induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The corresponding carbons were detected in the 13 C NMR spectrum at  = 147.1 and 117.1 ppm, respectively. The reaction of piperidine with 2-chloro-ethanol gave 4 [31][32][33][34] whose reaction with 3 afforded 5 as a colorless solid in 92% isolated yield. Desilylation of 5 with tetra-n-butylammonium fluoride trihydrate in THF yielded 6.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding carbons were detected in the 13 C NMR spectrum at  = 147.1 and 117.1 ppm, respectively. The reaction of piperidine with 2-chloro-ethanol gave 4 [31][32][33][34] whose reaction with 3 afforded 5 as a colorless solid in 92% isolated yield. Desilylation of 5 with tetra-n-butylammonium fluoride trihydrate in THF yielded 6.…”
Section: Resultsmentioning
confidence: 99%
“…During the past few decades, both natural and synthetic AQs have been studied for their anticancer properties, and some of them such as doxorubicin, daunorubicin and mitoxantrone are nowadays the rst-line treatment of many cancers [11]. The mechanism of action of AQs includes induction of aberrant cell metabolism, DNA damage, cell cycle arrest, apoptosis [12], paraptosis [13], autophagy [14], radiosensitization [15], decreased metastasis and invasion [16]- [18]. Doxorubicin and mitoxantrone are located in the cell nucleus, which is ascribed to the cationic alkylamino group responsible for its interaction with DNA [19].…”
Section: Introductionmentioning
confidence: 99%
“…Then it causes the release of cytochrome c. Cytochrome c is released into the cytosol and activates a family of caspases. Then a series of cascade reactions are triggered [17][18][19]. Studies have shown that the increased production of reactive oxygen species (ROS) also induces a decrease in the mitochondrial membrane potential, followed by the release of cytochrome c, which ultimately leads to apoptosis [20,21].…”
Section: Introductionmentioning
confidence: 99%